If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 2) + -16 = 21 + 5 Reorder the terms: -6(2 + x) + -16 = 21 + 5 (2 * -6 + x * -6) + -16 = 21 + 5 (-12 + -6x) + -16 = 21 + 5 Reorder the terms: -12 + -16 + -6x = 21 + 5 Combine like terms: -12 + -16 = -28 -28 + -6x = 21 + 5 Combine like terms: 21 + 5 = 26 -28 + -6x = 26 Solving -28 + -6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -6x = 26 + 28 Combine like terms: -28 + 28 = 0 0 + -6x = 26 + 28 -6x = 26 + 28 Combine like terms: 26 + 28 = 54 -6x = 54 Divide each side by '-6'. x = -9 Simplifying x = -9
| (8c-1)(6c-7)=0 | | 7(5y-2)=28y | | 2a^2+20=4 | | K^2-3K-28= | | 6x-7y=-8 | | K^2-3K-25= | | 23x=5 | | a/5-3=-12 | | a=.5(11+15)*6.9 | | (3h+2)(6h-5)=0 | | V^2-6V-27= | | 3(15+x)=60 | | 18=(8+.5)(w) | | V^2-15V+54= | | 6x+14x-28=-8 | | 25x-10+15=50 | | (5m-2)(m+3)=0 | | (5a^2-6a^3+5a)+(7a^4+2a^3-5a)= | | 0.9t=1+t | | 2x+33=10x-7 | | n^2+7n-18= | | 4x-5(x+1)+9=0 | | 2-3x=26 | | (k-6)(k+8)=0 | | -5+8x+1=3x-59 | | 0.5x+0.6=-10.9-1.8x | | Y=4x^2-12x-9 | | (a+8)(a-2)=0 | | 1.7+0.5x=0.9x-5.1 | | 3x+43=5x-9 | | 68-6x=21x+20 | | y=-x^2+14x-24 |